Tissue expression of aquaporin 2 is correlated to urine output and allograft function in sensitized kidney transplant patients - Klein, Katrin; Rübenacker, Stefan; Schäfer, Sebastian Markus; Kihm, Lars Philipp; Schwenger, Vedat; Macher-Göppinger, Stephan; Schemmer, Peter; Süsal, Caner; Zeier, Martin; Morath, Christian; Becker, Luis Eduardo (Transplantation proceedings, 2016)
Background - Salt and water disturbances often occur during acute kidney allograft dysfunction that contribute to graft failure, but this condition has been poorly investigated in the alloreactivity setting. We evaluated the tissue expression of aquaporins (AQP1 and AQP2) and the epithelial sodium channel (ENAC) in kidney biopsy specimens from sensitized kidney transplant recipients. - Methods - Eighty-six biopsy specimens from 33 sensitized patients were divided into 3 groups according to clinical context: time-zero (n = 9), protocol (n = 9), and indication (n = 68). The indication biopsy specimens were further divided into 3 subgroups according to the presence of acute tubular necrosis or rejection. Normal kidney tissue samples (n = 6) served as the control specimens. Immmunohistochemical expression of AQP1, AQP2, and ENAC was determined by using image analyzing software. - Results - Significantly lower AQP1 expression was observed in the time-zero and indication biopsy specimens with rejection compared with control specimens (P = .03 and P = .04, respectively). AQP2 expression was significantly lower in patients with an indication biopsy specimen compared with control and protocol biopsy specimens (P = .05 and P = .005). For ENAC, a lower expression was noted in the indication biopsy specimens compared with the control specimens (P = .04). Both AQP1 and AQP2 tissue expressions were significantly correlated to urine output (r = 0.45 and r = 0.32; P = .001 and P = .02), and AQP2 was correlated with the glomerular filtration rate estimated by using the Modification of Diet in Renal Disease Study equation at biopsy (r = 0.23; P = .05). - Conclusions - These findings partially confirm previous experimental data showing downregulation of AQP1 expression after ischemia/reperfusion injury and during rejection. AQP2 downregulation seems to be rejection-independent, occurring during deteriorating or poor kidney graft function.
Gesehen am 13.05.2020